SISTEM PAKAR DIAGNOSA KERUSAKAN HANDPHONE DENGAN MENGGUNAKAN METODE ALGORITMA BREADTH FIRST SEARCH - Suci Wahdaniah; Laila Qadriah; Zikrul Khalid (Jurnal Real Riset, 2023)
Expert System is a part of Artificial Intelligence (AI) which contains knowledge and experience that is put by one expert into a particular media knowledge, so that everyone can use it to solve various problems. One of them is diagnosing cellphone damage. Cellphones/smartphones are a basic necessity tool at this time, a powerful telecommunication medium in providing information and communication with everyone. The symptoms that are often faced by some cellphone users, such as slow cellphones, application/software errors, and cellphone restarts themselves. So, with this build an expert system application for diagnosing cellphone damage using the Breadth First Search Algorithm Method. The purpose of this study is to make it easier for the system to diagnose damage to find a solution, and will search for all nodes until it finds the right diagnosis, so that through this application, it can make it easier for technicians and cellphone/smartphone users to solve problems that occur on cellphones and provide information. regarding the symptoms of damage that occurs on cellphones. The design of this application is website-based using the PHP, HTML, CSS and JavaScript programming languages, as well as the use of a database server using MySQL. This expert system for diagnosing cellphone damage using the Best First Search Algorithm method can help and make it easier to check cellphones that are damaged so that they can provide solutions and more efficient maintenance. If the search for damage and symptoms does not find results in the form of solutions, the system will carry out further searches until solutions and information about damage and symptoms of cellphone damage are found.Keywords :Expert System, Diagnosis, Mobile, Breadth first Search, Website